'Attract thy fairy fingers near the lyre': Scripting and Performing Childhood in Byron's 'To Ianthe'. Issue 1 (June 2018) - McCune, Adam
Abstract : Byron scholars have observed that Byron commonly treats identities as performances rather than essences. However, excluding children from such performances of identity, scholars see Byron's 'To Ianthe' (1814) as a portrait of inherent childhood innocence. Byron's biographers and child studies scholars point out that portrayals of children as passively innocent expose the child character and child reader to exploitation by the adult author. I argue instead that in Byron's 'To Ianthe' the child does participate in the performance of identity. The poem describes many models of childhood—innocence, erotic desirability, cultured competence—presenting these different models of childhood to the reader as options: different roles the child reader may select to perform. Emphasising the child performer of roles over adult prescriptions for childhood, the poem treats all adult prescriptions as scripts subject to selection and adaptation by the child performer, demonstrating Byron's recognition of child agency.